PENGARUH KUALITAS PELAYANAN CUSTOMER SERVICE BANDARA I GUSTI NGURAH RAI BALI TERHADAP KEPUASAN WISATAWAN NUSANTARA - Ahmad, Faisal; Indrawati, Yayu; Mahadewi, NPE. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024)DO - 10.24843/IPTA.2024.v12.i01.p06, 2024)
This study aims to determine how much influence Customer Service has in serving in solving passenger problems and complaints at I Gusti Ngurah Rai International Airport in Bali based on existing SOP. As well as to find out how much influence this Customer Service Performance has in serving passengers at I Gusti Ngurah Rai Airport in Bali.This type of research uses descriptive quantitative analysis using multiple linear regression analysis. The data used are primary and secondary data. Data collection techniques are observation, questionnaires with 100 respondents distributed online, library research, and documentation. The sampling technique is purposive sampling and the data analysis tool in the study uses SPSS 26. The results of the research service quality variable (X) have a Sig value. 0.001 which is less than 0.05. From this value, it is rejected because there is an influence between service quality (X) on tourist satisfaction (Y) simultaneously. While the partial influence of Tangible (X1), Empathy (X2), Reability (X3), Responsiveness (X4), and Assurance (X5) partially has a positive and significant influence on tourist satisfaction using Customer Service (Y). From the tabulation of 21 indicators, the average value is 4.10 which is categorized as agree. And the highest indicator in the overall tabulation of this indicator is the friendliness of the staff in providing services with an average value of 4.21 which is rated as strongly agree. Meanwhile, the lowest indicator is the complete Customer Service Counter Facility indicator with an average of 3.83 which is categorized as agree.